Paraoxonase-1 Is Not Associated with Coronary Artery Calcification in Type 2 Diabetes: Results from the PREDICT Study. Issue 2 (23rd May 2013) - Mackness, Bharti; Marsillach, Judit; Elkeles, Robert S.; Godsland, Ian F.; Feher, Michael D.; Rubens, Michael B.; Flather, Marcus D.; Humphries, Steve E.; Cooper, Jackie; Mackness, Mike
Abstract : Objectives : To determine any association between serum paraoxonase-1 (PON1) activity, protein and coding region genetic polymorphisms and coronary artery calcification (CACS) and to determine factors which modulate serum PON1 in type 2 diabetes (T2DM). Methods and results : 589 patients (419 Caucasian, 120 South Asian, 50 other) from the PREDICT Study were investigated. All patients were asymptomatic for coronary disease and had established T2DM. CACS, lipids, lipoproteins, inflammatory markers, insulin resistance and PON1 activity, concentration and Q192R and L55M genotypes were measured. Independent associations were: 1) PON1 activity negatively with insulin resistance, triglycerides and PON1-55 genotype and positively with PON1-192 genotype; 2) PON1 concentration negatively with Caucasian ethnicity, duration of diabetes and statin use and positively with plasma creatinine and PON1-192 genotype. There was no association between CACS and any of the PON1 activity, concentration or genotype and this finding was not different in the various ethnic groups within the PREDICT study. Conclusion : PON1 is modulated by a number of factors, some of which are reported here for the first time, including ethnicity and insulin resistance in subjects with T2DM. No association between CACS and PON1 was found.